Giant Photoluminescence Enhancement of Ga‐Doped ZnO Microwires by X‐Ray Irradiation - Siyuan He; Shuiyan Cao; Ying Liu; Wenfa Chen; Pin Lyu; Weidian Li; Jincheng Bao; Wenhui Sun; Caixia Kan; Mingming Jiang; Yanpeng Liu (Advanced Science)
Abstract Ga‐doped zinc oxide (ZnO) microwires hold great promise for developing highly efficient light sources because of the wide bandgap with proper exciton binding energy. However, most microwires grown from one mainstream approach, i.e., chemical vapor deposition (CVD), are morphologically and crystallographically defective, exhibiting limited photoluminescence performances. Herein, a simple and effective X‐ray irradiation strategy is demonstrated for enhancing the photoluminescence of Ga‐doped ZnO microwire in ambient conditions. Under moderate doses (≤ 150 Gy), the photoluminescence monotonically rockets up with X‐ray dose increment and achieves nine‐fold enhancement at a dose of ≈150 Gy, recording high photoluminescence improvement of ZnO microwires to date. The elemental characteristics under different controlled irradiation atmospheres suggest the elimination of surface oxygen vacancy and the cross‐section transmission electron microscope reveals prominent lattice relaxations after mild X‐ray irradiation. In addition, the X‐ray irradiated microwires further exhibit elevated electroluminescence by over three times. The enhanced photoluminescence and electroluminescence as well as long‐term stability enable us to imagine the super‐rapid applications of ZnO microwires in modern optoelectronic devices.